2012
DOI: 10.1590/s1020-49892012000800004
|View full text |Cite
|
Sign up to set email alerts
|

Mortality trends from hypertension in Mexico by socioeconomic region and state, 2000-2008

Abstract: Age-adjusted mortality rates per 100 000 inhabitants who died from hypertension increased from 15.7 to 18.5 between 2000 and 2008, taking the world population age distribution as standard. Mortality was higher in women than in men and in individuals who did not complete elementary school than in those with more or no education. The strongest associations were in Mexico City, Oaxaca, and region 7.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…Many studies have focused on hypertension as morbidity; however, few have studied mortality from this cause. Of the 722,611 deaths reported in Mexico from all causes in 2018 6 , hypertension contributed 3.3%, and our results showed that the age of death has been advancing each year, as well as showing that hypertension-related mortality in Mexico has increased in the last 20 years, with a greater rise in men than in women, as has been previously reported 10 . This increase could be explained by the interaction with other cardio-metabolic diseases including diabetes, or to intrinsic sex-based differences in blood pressure management in Mexico (45.6%), which is lower overall compared to other countries 23 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Many studies have focused on hypertension as morbidity; however, few have studied mortality from this cause. Of the 722,611 deaths reported in Mexico from all causes in 2018 6 , hypertension contributed 3.3%, and our results showed that the age of death has been advancing each year, as well as showing that hypertension-related mortality in Mexico has increased in the last 20 years, with a greater rise in men than in women, as has been previously reported 10 . This increase could be explained by the interaction with other cardio-metabolic diseases including diabetes, or to intrinsic sex-based differences in blood pressure management in Mexico (45.6%), which is lower overall compared to other countries 23 .…”
Section: Discussionsupporting
confidence: 87%
“…In a study that considered 194 countries, including Mexico, it was reported that between 1990 and 2017, hypertension was responsible for the largest number of all-cause deaths, followed by smoking and high fasting plasma glucose 9 . A previous report on mortality trends in Mexico suggested that between 2000 and 2008, the age-adjusted mortality rate per 100,000 inhabitants increased from 15.7 to 18.5, being higher among women than men, and higher among people who did not complete primary school than those with more education 10 . To identify determinants which have impacted hypertension mortality rates in Mexico, the Age-Period-Cohort approach offers an advantage as it disentangles age, period and cohort-specific effects that allow for a better understanding of the potential modifiers of these trends, which could inform public policy to further reduce the burden of hypertension in Mexico 11 .…”
Section: Introductionmentioning
confidence: 96%
“…Physical and mental functioning is also better for the better educated. Among those with chronic conditions such as diabetes and hypertension, the better educated are more likely to have their condition under control Sánchez-Barriga 2012). Figure 4.3 also shows that education provides access to health information.…”
Section: Education and Health Literacymentioning
confidence: 99%